Pendidikan Karakter dalam Cerita Pendek Arab Anak Thahir dan Nadiya Karya Amin Salamah - Salsabila, Hanifah; Yuningsih, Yeni Ratna (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study focuses on the short story “Thahir and Nadiya” by Amin Salamah, which depicts the journey of two children as they struggle to find their way home after being abandoned in the forest by their parents. The aim of this research is to reveal the moral message and character education values contained in the story, so that they can serve as a source of reflection and be applied in children’s daily lives. The primary data in this research is the text of the short story “Thahir and Nadiya” by Amin Salamah, while secondary data is obtained from relevant journals, books, and other academic sources. The data were collected through documentation, involving careful reading and in-depth analysis of the text. The analysis uses Roland Barthes’ semiotic theory to examine three layers of meaning: denotative, connotative, and mythic. The result indicates that the short story conveys important character values, including care, affection, courage, intelligence, faith, empathy, perseverance, and patience. Therefore, this work not only possesses aesthetic value but also functions as an important and relevant medium for the development of children’s character in the present day.